Upaya Pendidikan Kesehatan Untuk Meningkatkan Pengetahuan Ny.M Tentang Hipertensi - MA'RUF, AMMAR, Supratman, Ph.D (2017)
Hypertension is high blood pressure that is abnormal with numbers ≥140 mmHg systolic and diastolic ≥90 mmHg. Hypertension occurs because of unhealthy lifestyle. Hypertension can be prevented through a healthy lifestyle. This can be done if a person has a good knowledge about hypertension. Advanced age is the final stage of a degenerative disease process, thus allowing for hypertension. The author of this paper aims to determine the level of nursing problems in hypertensive patients and providing health education to increase knowledge about hypertension. The method used isdescriptive include interview, observation, and data collection. The result is the author of the main problems arise aches, dizziness, feeling uneasy, worried, and the wrong diet. In dealing with these problems the author teaches how to provide health education on hypertension, this can help to identify and prevent problems that occur in peyakit hypertension. Know the problem of hypertension can be done by providing health education as an effort to increase knowledge.